2022
DOI: 10.1002/jemt.24187
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic (LM and SEM) visualization of pollen ultrastructure among honeybee flora from lower Margalla Hills and allied areas

Abstract: Microscopic visualization of micro‐morphological characters were analyzed using a scanning electron microscopic (SEM) tool, which has proven to be very successful to analyze the pollen surface peculiarities. The significant goal of this research was to perform microscopic examination of pollen of some of the most frequently visited honeybee floral species around apiaries. Micro‐morphological characterization of frequented honeybees foraged plants were discussed. A total of 15 species, belonging to 11 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The reticulate pattern increases the structural strength and surface friction coefficient of pollen, which helps them interact with insects and increases the ability of insects to carry the pollen (Attique et al, 2022). In our classification based on pollen quantitative characteristics, we found that polar axis length, equatorial axis length and pollen size played an important role in the classification of Impatiens, which was similar to the results of most plant pollen studies (Zafar et al, 2022).…”
Section: Pollen Characteristics Of Impatienssupporting
confidence: 84%
See 1 more Smart Citation
“…The reticulate pattern increases the structural strength and surface friction coefficient of pollen, which helps them interact with insects and increases the ability of insects to carry the pollen (Attique et al, 2022). In our classification based on pollen quantitative characteristics, we found that polar axis length, equatorial axis length and pollen size played an important role in the classification of Impatiens, which was similar to the results of most plant pollen studies (Zafar et al, 2022).…”
Section: Pollen Characteristics Of Impatienssupporting
confidence: 84%
“…The statistical data of Microsoft Excel YEAR (Redmond, WA, USA) were used, and SPSS 26.0 (IBM, Inc., Armonk, NY, USA) was used for correlation, principal component and system clustering analyses (Pérez-Gutiérrez et al, 2015;Zafar et al, 2022). The number of sepals (NS), which is one of the important bases for the classification of Impatiens, was added as a reference index to compare the importance of pollen characteristics during the analysis of indices.…”
Section: Data Statistics and Analysismentioning
confidence: 99%
“…Primarily, the investigation of morphological diversity in pollen is directly concerned with the classification of plants [18,19]. Palyno-morphological characteristics are fruitful for solving various taxonomic problems at species, genus, and family levels [7,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%